TET2 mutation does not impact the prognosis of adult acute myeloid leukemia patients receiving a hematopoietic stem cell transplantation in first remission: similar outcome following matched sibling and unrelated versus haploidentical donor transplants in a multi-center retrospective analysis from the Global Committee and the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation - Lin Li; Yishan Ye; Jacques-Emmanuel Galimard; Myriam Labopin; Depei Wu; Jia Chen; Nicolaus Kröger; Jakob Passweg; Urpu Salmenniemi; Maija Itäla-Remes; Xavier Poiré; Matthias Eder; et al. (Haematologica)
Not available.